In pursuit of the sustainable development goals : success stories of women entrepreneurs in emerging economies - Malhotra, Nishi; Saravanan, Palanisamy (Emerald Publishing Limited, 2025)
Until 2014, rural women in India had limited involvement in the country's economic growth. Prime Minister Narendra Modi's administration has worked to change that by making a notable shift towards female empowerment and equitable growth through initiatives like Atmanirbhar Bharat and Viksit Bharat 2047. This timely study showcases PM Modi's efforts in transforming rural development by empowering women through self-help groups, resulting in the exponential growth of female entrepreneurs. In Pursuit of the Sustainable Development Goals uses first hand interviews and real-world case studies to delve into how initiatives like self-help groups and community lending have empowered women and contributed to achieving the United Nations Sustainable Development Goals of poverty reduction (Goal 1) and women's empowerment (Goal 5). Additionally, the work uses case studies of women entrepreneurs from Rajasthan, Jammu and Kashmir, and Gujarat, to highlight their success in international markets through traditional crafts like Bandani, Pashmina, and Kannuj perfume. Key to this investigation is the importance of leadership, marketing strategies, and geographic indicators in transforming handicraft sectors and enhancing sustainability. Further, this work examines why women excel as risk managers within community lending groups, analysing leadership traits and the impact of gender-inclusive policies on achieving the Sustainable Development Goals. Highlighting the strategic management of community groups through success stories and real-life accounts communicated through first hand interviews, this work is essential reading for academic scholars, students and policymakers working in the areas of strategy and public policy as well as microfinance and development studies.
Includes index.
Keywords: Women-owned business enterprises -- India.; Business & Economics -- Women in Business.; Business innovation.; Business and Management.; Gender studies: women and girls.; elektronické knihy; electronic books